Dinamika Politik Proses Keputusan Impor Beras Tahun 2018 dan Tahun 2021 - Asran Jalal (Populis : Jurnal Sosial dan Humaniora, 2022)
The rice import decision process in 2018 and 2021, creates different view on government elites and government elites with non-government elites. The government elites are Presiden Jokowi, the Coordinating Minister for the Economy, the Trade Minister, the Agriculture Minister, the Director Bulog, and DPR. Non-government elites are political parties, observers, civil society. The focus this article is first, to discuss the differences in the views of the Minister of Trade against the Director of Bulog and the Minister of Agriculture regarding the rice impor decision process in 2018 and 2021. Second, to discuss President Jokowi’s decision to continue rice imports in 2018 and his decision to cancel rice imports in 2021. The argument of this paper is that the different views of government elites on the rice impor process in 2018 and 2021 are base on political-pragmatic interests versus ideolocal-stategic interests and interest of institution-organization. President Jokowi’s decision to cancel the to import rice in 2021, because the rejection of the plan did not only come from the DPR as government elites, the refusal also came from the political party elite as non-government elite.Proses keputusan impor beras pada tahun 2018 dan tahun 2021, menimbulkan perbedaan pandangan pada elite-elite pemerintah dan elite-elite pemerintah dengan elite-elite non-pemerintah. Elite-elite pemerintah dimaksud yaitu Presiden Jokowi, Menko Ekonomi, Menteri Perdagangan, Menteri Pertanian, Direktur Bulog, dan DPR. Elite-elite non-pemerintah yaitu partai politik, pemerhati, dan masyarakat sipil. Fokus artikel ini adalah: pertama, mendiskusikan perbedaan pandangan Menteri Perdagangan berhadapan Direktur Bulog dan Menteri Pertanian tentang proses keputusan impor beras tahun 2018 dan tahun 2021. Kedua, mendikusikan keputusan Presiden Jokowi melanjutkan impor beras tahun 2018 dan keputusannya membatalkan impor beras tahun 2021. Argumen tulisan ini adalah perbedaan pandangan elite-elite pemerintah dalam proses impor beras tahun 2018 dan 2021 dilandasi kepentingan politis-pragmatis versus kepentingan ideologis-strategis dan kepentingan organisasi-institusi. Keputusan Presiden Jokowi membatalkan rencana impor beras tahun 2021, karena penolakan rencana tersebut bukan hanya berasal dari DPR sebagai elite-elite pemerintah, penolakan juga datang dari elite partai politik sebagai elite non-pemerintah.